Study of the in vitro release profile of sesquiterpenes from a vaginal cream containing Copaifera duckei Dwyer (Fabaceae) oleoresin - Helison Oliveira Carvalho, Clarissa Silva Lima, Anderson Almeida Sanches , Jocivania Oliveira da Silva, Caio Pinho Fernandes, Jose Carlos Tavares Carvalho (Journal of Applied Pharmaceutical Science, 2015)
Copaiba trees and their oleoresin is an important natural product used as an anti-inflammatory and antimicrobial drug, in particular for gynecological infections. The in vitro release profile of sesquiterpenes in a vaginal cream containing copaiba (CVC – copaiba vaginal cream) oleoresin in buffered solutions at different pHs was evaluated in the present study. The dissolution test revealed that trans-caryophyllene (TC) was constantly released until the final test time. The maximum peaks were found at a concentration of 478.79 nL/mL for the buffer at pH 5 and at a concentration of 475.99 nL/mL for the buffer at pH 6, with a percentage release of 50.52% and 50.21%, respectively. Likewise, the caryophyllene oxide (CO) was released into the buffers at pHs 5 and 6, with maximum release peaks at 60 minutes at a percentage of 31.8% and 33.5% corresponding to concentrations of 2.779 and 2.925 μg/mL, respectively. The release and dissolution profiles of the sesquiterpene compounds indicated that a pH of 5-6 in the dissolution media is adequate for release of these markers of antimicrobial activity in Copaifera duckei Dwyer. Therefore, these conditions possibly favor the therapeutic action of CVC.
Keywords: Copaifera, oleoresin, sesquiterpenes, dissolution.